Making Smectic Defect Patterns Electrically Reversible and Dynamically Tunable Using In Situ Polymer‐Templated Nematic Liquid Crystals. Issue 11 (7th June 2021) - Boniello, Giuseppe; Vilchez, Victoria; Garre, Emmanuel; Mondiot, Frédéric
Abstract : Back Cover : In article number 2100087 by Frédéric Mondiot and co‐workers, in situ polymerization of voltage irreversible smectic A defect patterns such as focal conic domains is utilized to transfer them into more electrically responsive nematic liquid crystals. Using this approach, linear arrays of elliptic‐hyperbolic focal conic domains with uncovered hiding properties can then reversibly switch back and forth with low voltages between textures ranging from totally hiding to transparent states.